Site occupancy of native terrestrial mammals in oil palm landscapes is driven by the synergy of land sparing and sharing strategies - Narayana, Satya; Affandi, Amir; Syafiq Yahya, Muhammad; Azmi Tohiran, Kamil; Jambari, Asrulsani; Razi Norhisham, Ahmad; Md Sharif, Badrul Azhar (Elsevier, 2024)
The conversion of tropical rainforests into industrial oil palm monocultures has detrimental effects of local biodiversity. Although some medium-sized mammals have demonstrated a degree of adaptability in oil palm landscapes, the factors that influence their ability to persist in such human-altered environments remain obscure. Here, we investigated the site occupancy and activity pattern of the mammals in oil palm landscapes in Peninsular Malaysia. We deployed 81 camera traps throughout six oil palm cultivation areas with two distinct management styles (three sites each in organized smallholdings and industrial plantations). Smallholdings had higher site occupancy of native animal species than industrial plantations. The site occupancy of the mammals was influenced by the proximity to continuous forest, forest patches and riparian vegetation. Landscape metrics are characteristics that affect land sparing strategy, allowing wild animals in agricultural landscapes to thrive in their habitat despite human threats. At stand-level, the detection of animals was determined by elevation, undergrowth vegetation cover/height, canopy cover, oil palm height, quantity of oil palm fruits, and prune stack thickness. Mammal occupancy was higher in the smallholdings due to the proximity to continuous forest. We recommend improving landscape heterogeneity and connectivity in oil palm matrix to promote species mobility and diversifying oil palm management away from monoculture farming. Our findings indicate that incorporating land sharing and sparing strategies into the oil palm matrix is necessary to conserve biodiversity and maintain ecological services. This implies that industry stakeholders ought not to disregard either land sparing or land sharing.